Hidden diversity of giant scydmaenines: five new species and new records of Clidicus in the Philippines (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł; Cheng, Zhi-Fei; Brajczewska, Nastazja; Yin, Zi-Wei (Zootaxa, 2019)
Until now, two species of Clidicus were known to occur in the Philippines, both inhabiting Mindanao. The scarcity of published records (merely six known Philippine specimens of this genus) suggested that Clidicus was rare in this country. We here falsify this view, by describing five new species and providing new records of the previously known species, based on a material of over 80 specimens collected on Mindanao and Luzon. Clidicus forceps Cheng, Yin & Jałoszyński, sp. n., C. interfector Jałoszyński, Cheng & Yin sp. n., C. kalis Jałoszyński, Cheng & Yin sp. n., C. occisor Jałoszyński sp. n., and C. shavrini Jałoszyński sp. n., are described. Clidicus crocodylus Jałoszyński, previously known to occur on Mindanao, is for the first time recorded in Luzon.